Complement factor H serum levels determine resistance to pneumococcal invasive disease - van,der Maten E; Westra,D; van,Selm S; Langereis,JD; Bootsma,HJ; van,Opzeeland FJ; de,Groot R; Ruseva,MM; Pickering,MC; van,den Heuvel LP; van,de Kar NC; de,Jonge MI; et al. (Journal of Infectious Diseases, 2016)
Streptococcus pneumoniae is a major cause of life-threatening infections. Complement activation plays a vital role in opsonophagocytic killing of pneumococci in blood. Initial complement activation via the classical and lectin pathways is amplified through the alternative pathway amplification loop. Alternative pathway activity is inhibited by complement factor H (FH). Our study demonstrates the functional consequences of the variability in human serum FH levels on host defense. Using an in vivo mouse model combined with human in vitro assays, we show that the level of serum FH correlates with the efficacy of opsonophagocytic killing of pneumococci. In summary, we found that FH levels determine a delicate balance of alternative pathway activity, thus affecting the resistance to invasive pneumococcal disease. Our results suggest that variation in FH expression levels, naturally occurring in the human population, plays a thus far unrecognized role in the resistance to invasive pneumococcal disease.